Interesterified fat consumption since gestation decreases striatal dopaminergic targets levels and gdnf impairing locomotion of adult offspring. (15th March 2021) - D'avila, Lívia Ferraz; Dias, Verônica Tironi; Milanesi, Laura Hautrive; Roversi, Karine; Trevizol, Fabíola; Maurer, Luana Haselein; Emanuelli, Tatiana; Burger, Marilise Escobar; Segat, Hecson Jesser
Graphical abstract: Highlights: IF consumption modifies the brain fatty acids composition. IF in early stages of life impairs sensorimotor development. IF chronic consumption decreases locomotion in adulthood. Lifelong IF consumption decreases D2R levels in striatum. IF chronic consumption reduces striatal GDNF immunoreactivity. Abstract: Interesterified fat (IF) currently substitutes the hydrogenated vegetable fat (HVF) in processed foods. However, the IF consumption impact on the central nervous system (CNS) has been poorly studied. The current study investigated connections between IF chronic consumption and locomotor impairments in early life period and adulthood of rats and access brain molecular targets related to behavior changes in adulthood offspring. During pregnancy and lactation, female rats received soybean oil (SO) or IF and their male pups received the same maternal supplementation from weaning until adulthood. Pups' motor ability and locomotor activity in adulthood were evaluated. In the adult offspring striatum, dopaminergic targets, glial cell line-derived neurotrophic factor (GDFN) and lipid profile were quantified. Pups from IF supplementation group presented impaired learning concerning complex motor skill and sensorimotor behavior. The same animals showed decreased locomotion in adulthood. Moreover, IF group showed decreased immunoreactivity of all dopaminergic targets evaluated and GDNF, along with important changes in FA composition in striatum . This study shows that the brain modifications induce by IF consumption resulted in impaired motor control in pups and decreased locomotion in adult animals. Other studies about health damages induced by IF consumption may have a contribution from our current outcomes.